Time partitioning among neotropical frugivorous bats: effects of phylogeny, body size, and abundance: Partición del tiempo entre murciélagos neotropicales frugívoros: efectos de la filogenia, el tamaño corporal y la abundancia - Cano, Manuel Francisco; Murillo-García, Oscar E. (Revista de Biología Tropical, 2021)
Introduction: Resource partitioning by promoting coexistence is essential to determine species richness and composition in natural communities. However, the partitioning of time has been questioned as a mechanism that promotes the coexistence of ecologically similar species. Objective: To determine the importance of the partitioning of time as a mechanism that promotes coexistence, we compared the activity patterns of tropical frugivorous bats. Methods: We captured bats with mist nets from sunset to sunrise in three study sites (tropical dry forest, wet forest, and rainforest) to calculate activity patterns of the species using Kernel density estimation. We used the superposition coefficient (Δ1) to compare activity patterns between (1) bat assemblages of study sites, (2) frugivorous species in the same site, and (3) populations of the same species among different sites. To determine whether the overlap in the activity patterns was related to the ecological similarity of species, we evaluated the association between Δ1 and similarity in abundances and body mass and phylogenetic closeness. Results: We found geographical variations in the overall activity patterns of the assemblages of the three localities. Likewise, we found variations in activity patterns between species at each study site and between populations in different study sites. Overlap in activity patterns tended to decrease as species were phylogenetically more closely related and similar in abundance and body size. Conclusions: Our results provide empirical support for the role of temporal segregation in activity patterns as a mechanism that promotes the coexistence of ecologically similar species in nature.